An examination of the links between corporate social responsibility (CSR) and its internal consequences - Kim, H.; Rhou, Y.; Uysal, Muzaffer; Kwon, N. (Pergamon, 2017)
The purpose of this study is to examine the links between Corporate Social Responsibility (CSR) and its internal consequencesusing the hotel employees' CSR perception, Quality of Working Life (QWL), affective commitment, organizational citizenship behavior (OCB), and job performance. Although CSR has been widely studied from the perspective of employees, no previous study has related it to QWL in the field of hospitality research. Applying relevant theories, the study empirically substantiates the connection between the constructs and provides theoretical and practical implications. The results, drawn from data collected from hotel employees in upscale hotels in South Korea, show that hotel employees' CSR perception of the firm positively influences their QWL, affective commitment, and organizational citizenship behavior, which, in turn, enhance their job performance.